1997
DOI: 10.2172/493372
|View full text |Cite
|
Sign up to set email alerts
|

Colloid suspension stability and transport through unsaturated porous media

Abstract: Executive SummaryContaminant transport is traditionally modeled in a two-phase system: a mobile aqueous phase and an immobile solid phase. Over the last 15 years, there has been an increasing awareness of a third, mobile solid phase. This mobile solid phase, or mobile colloids, are organic or inorganic submicron-sized particles that move with groundwater flow. When colloids are present, the net effect on radionuclide transport is that radionuclides can move faster through the system. It is not known whether mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…These experiments have investigated the effect of the degree of moisture saturation (Kaplan et al 1996, Gamerdinger et ai. 1998), pH (Kaplan et al l996,1998a, 1998b, mobile colloids (McGraw andKaplan 1997, Lee et al 1998), ionic strength (Kaplan et al 1995(Kaplan et al , 1998b, radionuclide concentration (Kaplan et al 1996), and sediment properties on the geochemical behavior of key radionuclides (Parker 1997). All these parameters are known to affect sorption of solutes, but the degree to which they do so in Hanford Site sediments, or more specifically in ILAW-DC sediments, is not known.…”
Section: Introductionmentioning
confidence: 99%
“…These experiments have investigated the effect of the degree of moisture saturation (Kaplan et al 1996, Gamerdinger et ai. 1998), pH (Kaplan et al l996,1998a, 1998b, mobile colloids (McGraw andKaplan 1997, Lee et al 1998), ionic strength (Kaplan et al 1995(Kaplan et al , 1998b, radionuclide concentration (Kaplan et al 1996), and sediment properties on the geochemical behavior of key radionuclides (Parker 1997). All these parameters are known to affect sorption of solutes, but the degree to which they do so in Hanford Site sediments, or more specifically in ILAW-DC sediments, is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Application of polyphosphate technology to vadose zone and capillary fringe environments for remediation requires understanding the effects of water content and pore water velocity on polyphosphate mobility, both of which have been previously shown to be significant influences on the mobility of reactive species within the subsurface Gamerdinger et al 1998;Gamerdinger et al 2001b;a;Lindenmeier et al 1995;McGraw 1996;McGraw and Kaplan 1997;Wellman et al 2008a). The only identified investigation of phosphate mobility under hydraulically unsaturated conditions indicated that phosphate application to sediments increased the water retention properties of the sediments as a result of the increase in the negative charge of the soil particles (Lutz et al 1966).…”
Section: 2mentioning
confidence: 99%
“…In a study by McGraw and Kaplan (1997), it was demonstrated that colloids are unlikely to remain suspended in glass leachate, cement leachate or Hanford groundwater because the ionic strength of these solutions greatly exceeded the critical flocculation concentration (the minimum electrolyte concentration to induce colloid flocculation) of most particles.…”
Section: Colloid-facilitated Transportmentioning
confidence: 99%